2008
DOI: 10.1186/1757-1146-1-13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foot orthoses on lower extremity kinetics during running: a systematic literature review

Abstract: Background: Throughout the period of one year, approximately 50% of recreational runners will sustain an injury that disrupts their training regimen. Foot orthoses have been shown to be clinically effective in the prevention and treatment of several running-related conditions, yet the physical effect of this intervention during running remains poorly understood. The aim of this literature review was therefore to evaluate the effect of foot orthoses on lower extremity forces and pressure (kinetics) during runni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 70 publications
(90 reference statements)
0
28
0
1
Order By: Relevance
“…Six involved different posting and moulding features20 30 32 and the other compared a posterior post with an anterior post (table 5). 11…”
Section: Resultsmentioning
confidence: 99%
“…Six involved different posting and moulding features20 30 32 and the other compared a posterior post with an anterior post (table 5). 11…”
Section: Resultsmentioning
confidence: 99%
“…Yet, certain main themes can be extracted from these studies. Recent literature surveys [6,7] concluded that FO generally have an attenuating effect on the peak impact vertical force and loading rate. Commonly reported kinematic effects normally relate to ankle joint sagittal plane movements, rearfoot frontal plane and tibial transverse plane movements [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that wearing foot orthoses leads to reduced loading in the lower limb via alterations to neuromechanical function (23,27). Previous studies examining the effect of foot orthoses on muscle activation patterns have been conducted during walking and running (25,26,28), in a nonfatigued state.…”
mentioning
confidence: 99%